Venous valve stent analysis - Chia, Mark Wen Hao (Nanyang Technological University, 2020)
Venous valve in the lower extremities such as the legs can fail to function properly and thereby limiting the circulation of blood flow from the legs up to the heart. This medical condition is known as Chronic Venous Insufficiency (CVI). There are treatments that can be administered that could limit the progression of existing clots, but when it is not working as intended. And the patient develops an acute condition, a possible option would be to do a minimally invasive surgical procedure of venous stenting. This project aims to investigate the optimisation of the venous valve stent models through the test of its structural effectiveness using Finite Element Analysis (FEA). The scope of the project includes: 1) Do a modification / redesign of venous stents models in with use of Solidworks. 2) Import the venous stent models into ANSYS for equivalent stress and deflection test simulation under boundary pressure conditions. 3) Investigate the equivalent stress and deflection of the various venous stent designs.Find a correlation between number of crowns and structural performance of the stent. Therefore, in this report, the overview of the methodology in designing the venous valve stent were presented and reviewed. The issues of conducting the Finite Element Analysis (FEA) and the findings concluded from the various designs when subjected to the static structural analysis. Using the method of additive manufacturing (3D Printing), as a possible fabrication technique for stent.